Surgical management of ovarian teratomas in childhood: a multicentric study on 110 cases and a literature review. (3rd October 2021) - Spinelli, Claudio; Strambi, Silvia; Masoni, Benedetta; Ghionzoli, Marco; Bertocchini, Alessia; Sanna, Beatrice; Morganti, Riccardo; Messina, Mario; Molinaro, Francesco; Tursini, Stefano; Briganti, Vito; Lisi, Gabriele; et al.
Abstract: Aim of the study: To compare a multicentric surgical experience on ovarian teratomas in childhood with the current management trends. Design: A retrospective multicentric pediatric ovarian teratomas surgically treated between January 2000 and August 2020 at four Italian institutions. PubMed database was used to search for Reviews and Systematic Reviews published between January 2010 and August 2020: 15 manuscripts reported 3633 ovarian neoplasms in pediatric age, 1219 (33, 5%) of which were ovarian teratomas. Results: A hundred-ten patients with a mean age at diagnosis of 11.8 years were enrolled. Mature cystic teratomas accounted for the 90% of the masses. At surgery, 78 were oophorectomies and 32 were ovary sparing surgeries. Laparoscopy occurred in 16.3% of the surgeries. As regarding the current management trends, the mean age at diagnosis was 11.9 years and 80.5% of the cases were represented by mature teratomas. Of 430 procedures, 331 were oophorectomies while 99 were ovary sparing surgeries and laparoscopy was performed in 23.8% of cases. Conclusions: Ovary-sparing surgery with laparoscopic approach is increasingly offered as standard treatment for benign masses that fit the criteria for mature teratomas, in the attempt to achieve the best compromise between the preservation of fertility and the prevention of recurrences. Awareness should be raised among pediatric surgeons to reduce unnecessary radical surgery.